Sleep Disturbance in Mild Cognitive Impairment and Association With Cognitive Functioning. A Case-Control Study - Palmer, Katie; Mitolo, Micaela; Burgio, Francesca; Meneghello, Francesca; Venneri, Annalena (Frontiers in Aging Neuroscience, 2018)
Objectives: The aims of the current study are to 1) report the frequency of specific sleep disturbance symptoms in MCI and cognitive healthy older persons; 2) examine whether overall poor sleep and specific sleep disturbance symptoms are more common in persons with MCI compared to cognitive healthy older controls and; 3) to examine the association between sleep disturbances and performance in general and specific cognitive domains in persons with MCI and separately in cognitive healthy older persons. Methods: Data were collected at the Fondazione Ospedale San Camillo Istituto di Ricovero e Cura a Carattere Scientifico (IRCCS), Venice, Italy as part of the European VPH-DARE@IT project. We included 69 persons with MCI (mean age 75.7; SD=7.7) and 72 sex-matched cognitively healthy controls (mean age 71.8; SD=7.0). Participants underwent extensive neuropsychological assessment as well as evaluation of subjective sleep performance with the Sleep Continuity in Alzheimer’s Disease Scale (SCADS). Results: A fifth of MCI patients (21.7%, n=15) had poor sleep compared to 15.3% (n=11) of cognitively healthy controls. MCI patients had a 3.2 higher odds of having poor sleep compared to cognitively healthy controls after adjustment for age, education, sex and general cognitive functioning (Odds Ratio (OR)=3.2; 95% Confidence Interval (CI)=1.1-9.2). Persons who reported waking up twice or more during the night had a higher odds of being MCI compared to those who never wake or wake only once (OR=2.6; 95% CI=1.1-6.1). In MCI patients, poor sleep was associated with better general cognitive functioning and short-term working memory, whereas in cognitive healthy older persons poor sleep was associated with impairment in episodic memory performance and executive functioning. Discussion: Our results confirm previous studies showing that sleep disturbances are common in MCI, and this may be due to an ongoing neurodegenerative process rather than a symptom of cognitive impairment. Future research with objective sleep measurements are needed in MCI as well as interventions to improve sleep with the aim of preventing cognitive decline.